2021
DOI: 10.1002/hep.31738
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of the Lysophosphatidylcholine/Autotaxin/Lysophosphatidic Acid Axis in Acute‐on‐Chronic Liver Failure Is Associated With Mortality and Systemic Inflammation by Lysophosphatidic Acid–Dependent Monocyte Activation

Abstract: BaCKgRoUND & aIMS: Acute-on-chronic liver failure (ACLF) is characterized by systemic inflammation, monocyte dysfunction, and susceptibility to infection. Lysophosphatidylcholines (LPCs) are immune-active lipids whose metabolic regulation and effect on monocyte function in ACLF is open for study. appRoaCHeS & ReSUltS:Three hundred forty-two subjects were recruited and characterized for blood lipid, cytokines, phospholipase (PLA), and autotaxin (ATX) concentration. Peripheral blood mononuclear cells and CD14 + … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 52 publications
4
27
0
Order By: Relevance
“…Moreover, LPA induced the production of proinflammatory cytokines by CD14+ cells without increasing phagocytic capacity. Altogether these data suggest a pivotal role of the LPC-ATX-LPA axis in the immune dysfunction observed in ACLF that could be corrected through modulation of the axis ( 129 ) ( Figure 2 ). The evidence of lysophospholipids involvement in ACLF and their potential therapeutic implications have been summarized in Table 2 .…”
Section: Lysophospholipidsmentioning
confidence: 85%
See 2 more Smart Citations
“…Moreover, LPA induced the production of proinflammatory cytokines by CD14+ cells without increasing phagocytic capacity. Altogether these data suggest a pivotal role of the LPC-ATX-LPA axis in the immune dysfunction observed in ACLF that could be corrected through modulation of the axis ( 129 ) ( Figure 2 ). The evidence of lysophospholipids involvement in ACLF and their potential therapeutic implications have been summarized in Table 2 .…”
Section: Lysophospholipidsmentioning
confidence: 85%
“…In ACLF, we recently reported that LPC-ATX-LPA axis modulates innate immunity (see below). Innate immunity is known to be associated with outcome in ALF ( 129 , 283 ), thus the study of LPC-ATX-LPA in this setting could be of great interest. Lysosphingolipids seem indeed related to multiple aspects of ALF and particularly hepatocyte death, mitochondrial and immune dysfunctions, however further studies are needed to elucidate the mechanisms involved.…”
Section: Lysophospholipidsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the LPS-induced acute lung injury mouse model, on the other hand, genetic or pharmacologic targeting of ATX had only minor effects on disease severity [42]. In contrast, there is evidence that a dysregulated ATX/LPA axis (decreased LPC, increased ATX expression and LPA concentration) in acute-on chronic liver failure (ACLF) associates with mortality and systemic infection [43]. The same group reported that LPS stimulates ATX gene expression and increases the inflammatory phenotype of monocytes that are isolated from ACLF patients [43].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, there is evidence that a dysregulated ATX/LPA axis (decreased LPC, increased ATX expression and LPA concentration) in acute-on chronic liver failure (ACLF) associates with mortality and systemic infection [43]. The same group reported that LPS stimulates ATX gene expression and increases the inflammatory phenotype of monocytes that are isolated from ACLF patients [43]. In line with this, it was demonstrated that LPS induces a massive increase in ATX mRNA and protein expression via autocrine IFN-γ signaling in monocytic THP-1 cells [44].…”
Section: Discussionmentioning
confidence: 99%